Language and Politicking: A Pragmatic Analysis of Political Texts in Political Posters and Jingles in Oyo State, Nigeria - Michael, Ajayi Temitope; Oluwafemi, Ajayi Daniel (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This paper attempts a pragmatic analysis of political texts in political posters of gubernatorial candidates for 2015 General Elections in Oyo state, Nigeria, within the purview of Mey’s (2001) Pragmatic Acts Theory. Data were collected from political posters of Governor Abiola Ajimobi(the incumbent governor of the state), the erstwhile governors of the state, Rasheed Ladoja and Alao Akala, and Professor Adejumo, a yet to be declared PDP’s gubernatorial candidate for the said election. The study reveals that the language of politicians in the state is characterised by practs such as accusation, challenge, abuse, warning and persuasion, commendation and condemnation which draw on contextual features such as Shared Situational Knowledge (SSK), Shared Cultural Knowledge (SCK), Metaphor (MPH) and Relevance (REF). The paper concludes that politicians in the state, an indication of what happens on a large scale in the country, employ language to attack one another’s personalities, rather than address issues that could help move the state forward.